Estimating the influence of dietary composition and management on nutrient intake and excretion and methane emission in different pig categories - Saman Lashkari; Frederik R. Dalby; Uffe Krogh; Elvira Sattarova; Christian F. Børsting (PLoS ONE, 2025)
The study aimed to estimate the effect of diet composition, pig production stage, in-housing conditions, and manure management on methane (CH4) emissions from enteric fermentation, manure stored in the barn, and the outdoor storage tank. For each pig category, an estimation for emissions was made for a standard Danish pig diet based on wheat, barley, and soybean meal. Within each category of pigs, emissions were also estimated for diets with different levels and types of dietary fiber from sugar beet pulp, wheat bran, oats, wheat, or soy hulls, which were included as a partial substitution for wheat or barley. In all diets within four pig categories, feed intake, excreted dry matter, feces mass, and urine volume (g/d per animal) increased in sugar beet pulp, wheat bran, oat, or soy hull diets compared to the average Danish diet. In grower-finisher pigs, the sum of CH4 emissions from enteric fermentation, manure stored in the barn, and the outdoor storage tank were 9.8, 10.2, 11.0, 11.0, and 11.2 (kg/year/animal place) for wheat diet, average Danish diet, oat diet, wheat bran diet, and sugar beet pulp diet, respectively, while in gestating sows, were 16.9, 17.5, 18.4, 19.6, 19.7, and 23.2 (kg/year/animal place) in wheat diet, average Danish diet, oat diet, sugar beet pulp diet, wheat bran diet, and soy hull diet, respectively. Contribution of CH4 emissions from manure stored in the barn plus outdoor storage tank for the average Danish diet accounted for 95, 90, 83, and 84% of total CH4 emissions in weaned pigs, grower-finisher pigs, lactating sows, and gestating sows, respectively. In conclusion, feed composition has a considerable impact on CH4 emissions. Enteric CH4 and CH4 emissions from manure stored in the barn and in the outdoor storage tank were increased by elevated concentration of residual fiber in all four pig categories except for enteric CH4 in weaned pigs.